1975
DOI: 10.1007/bf02532762
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of phospholipid composition ofAedes aegypti andAedes albopictus cells obtained from logarithmic and stationary phases of growth

Abstract: Aedes aegypti and Aedes albopictus cells were grown in tissue culture and harvested at logarithmic and stationary phases of development. The phospholipids were extracted, separated into lipid classes, and fatty acid composition of each fraction determined. The phosphatidylethanolamine fraction was the major lipid (42-54%). With aging, the A. aegypti cells showed an increase in polyenes in the phosphatidylcholine and phosphatidylethanolamine fractions and in monoenes and polyenes in the phosphatidylinositol fra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

1976
1976
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 13 publications
2
9
0
Order By: Relevance
“…This distribution is similar to the membrane lipid composition of eukaryotic cells where the most abundant phospholipid is PC [21]. It is also consistent with the membrane lipid composition of the Diptera species where PE is a predominant PL [22]. CER-PE, which is preferentially expressed in insect cells, is also observed here [23][24].…”
Section: Author Summarysupporting
confidence: 88%
See 1 more Smart Citation
“…This distribution is similar to the membrane lipid composition of eukaryotic cells where the most abundant phospholipid is PC [21]. It is also consistent with the membrane lipid composition of the Diptera species where PE is a predominant PL [22]. CER-PE, which is preferentially expressed in insect cells, is also observed here [23][24].…”
Section: Author Summarysupporting
confidence: 88%
“…There was also limited overlap between the specific PE molecular species regulated between DENV-and UV-DENV-exposed cells (Table S1). Given that insect cells have a high abundance of PE in their membranes (40-50%), it is interesting that there is a selective requirement for PC (over PE) in DENV-infected mosquito cells [22].…”
Section: Author Summarymentioning
confidence: 99%
“…Similarity in enzyme subcellular localizations, membrane and endomembrane compositions also suggest a certain homology in lipid biosyntheses ( Butters and Hughes, 1981 ). Aedes mosquito cells contain an abundance of PC and PE and the same PL categories as in mammals ( Townsend et al, 1972 ; Jenkin et al, 1975 ). However, while PC is the main PL in mammalian cells, Aedes mosquito cells contain a majority of PE ( Luukkonen et al, 1973 ; Jenkin et al, 1975 ; Dawaliby et al, 2016 ), and other substantial differences in lipid metabolism between insects and mammals exist ( Canavoso et al, 2001 ).…”
Section: Flaviviruses Subdue Phospholipids In Mosquitoesmentioning
confidence: 99%
“…We examined the EM map in the vicinity of the pocket and found that it is occupied by strong density resembling the headgroup of a phosphatidylethanolamine lipid (PE), with partially resolved fatty acid tails (Fig 4b, c). PE is the most abundant phospholipid in the lipidome of Aedes aegypti and Aedes albopictus cells 31 .…”
Section: Rearrangement Of Amphipathic Helices Leads To Formation Of Amentioning
confidence: 99%